Sistem Penunjang Keputusan Seleksi Atlet Berdasarkan Data Fisik Menggunakan Naïve Bayes - yosia halundaka; Din Syamsudin; Aryo Nugroho (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2020)
The purpose of this observation was to predict the passing rate of the physical test results of the participants of the martial arts athlete organized by KONI. The researchist made a classification based on data obtained from trainer of physical martial arts Kempo by using data mining. Data mining can be interpreted is a process extractcing new informartion was taken from big chunk of data for support the results of making decision support systems. Therefor using decision support systems which can help make a decision to choose the best athlet. In data mining there are many methods that can be used, one of them is the classification method by using alogarithms naive bayes. The results obtained from this observation is Correctly Classified Instances 94.4% with speed presentase 60% and 70% bring out Correctly Classified Instances 92.85%, while speed presentase 80% bring out Correctly Classified Instances 88.89%.